Le défi - Trudeau, Pierre (Les Cahiers de droit, 1985)
This speech was given by the Prime Minister at the closing banquet of the Conference on the Reform of Federal Institutions in Quebec on March 30, 1984. He suggested that Reform is desirable because Canadian Federalism is capable of evolution and renewal. Canada needs institutions in which a national consensus on its fundamental options can be developed frankly and openly. The federal government's representativeness and its authority to speak and act in the name of all regions and of all Canadians must be strengthened. The proposed reform of the Upper House conducted by the Special joint Committee on Senate Reform indicates that provinces and regions should be represented adequately, not the provincial governments. These governments, because regional interests were not perceived to be adequately represented within the federal institutions, have had a tendency to present themselves as the only legitimate representatives of the regions. The idea of a second chamber elected directly by the people would enhance the independence and authority of senators in their role as regional representative. Mr. Trudeau indicates that the institutionalization of federal-provincial conferences ought to be looked at with the aim of harmonizing the policies of the two orders of government. This should establish coordination and effective management in areas of shared jurisdiction.